(untitled) (CR. Conservación y Restauración, 2025)
Faced with the incessant loss of the country’s material memory popular wisdom affirms “prevention is better than regret”, for this reason the information campaign What do we lose when our cultural heritage is stolen? emphasizes preventive actions to avoid the theft of cultural heritage. In 2020, the Coordinación Nacional del Patrimonio Cultural (CNCPC) of the Instituto Nacional de Antropología e Historia (INAH) launched an information campaign to invite civil society to help protect Mexico’s cultural heritage. The campaign was designed to draw the population’s attention to the problem, to disseminate information related to reporting theft and illicit trafficking of cultural property among the groups that protect and use it. The participation of society is extremely important to stop the theft and illicit trafficking of cultural heritage, since the institutions that protect this legacy require society to make a common front against those who seek to appropriate the pieces that are part of the history of a nation. Preventing, protecting, and reporting are actions that we can all carry out, the question is to be informed to know how to react.